2002
DOI: 10.1016/s0735-1097(02)01727-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy restores optimal atrioventricular mechanical timing in heart failure patients with ventricular conduction delay

Abstract: We characterized the relationship between systolic ventricular function and left ventricular (LV) end-diastolic pressure (LVEDP) in patients with heart failure (HF) and baseline asynchrony during ventricular stimulation. The role of preload in the systolic performance improvement that can be obtained in HF patients with LV stimulation is uncertain.We measured the maximum rate of increase of LV pressure, LVEDP, aortic pulse pressure (PP) and the atrioventricular mechanical latency (AVL) between left atrial syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 15 publications
2
124
0
5
Order By: Relevance
“…[1][2][3][4][5][6] These pioneering small studies paved the way for large randomized controlled trials that demonstrated reductions in morbidity and mortality in heart failure. [7][8][9][10][11][12][13] Surprisingly, the effects of biventricular pacing on coronary blood flow have been little studied.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] These pioneering small studies paved the way for large randomized controlled trials that demonstrated reductions in morbidity and mortality in heart failure. [7][8][9][10][11][12][13] Surprisingly, the effects of biventricular pacing on coronary blood flow have been little studied.…”
mentioning
confidence: 99%
“…Although AV-delay optimisation can clearly impact hemodynamics in patients undergoing CRT, (32,33) it has less infl uence on LV function than the optimal pacing site (34) . An optimal AV delay is that which allows completion of the end-diastolic fi lling fl ow prior to ventricular contraction, thereby providing the longest diastolic fi lling time.…”
Section: Optimising Atrio-ventricular Delaymentioning
confidence: 99%
“…It has been recommended that the VV-interval be optimised before the AVinterval, to prevent inappropriate AV-delay programming, which might reduce LV fi lling (33) .…”
Section: Vol 4 No 2 2007mentioning
confidence: 99%
“…CRT reduces clinical symptoms of heart failure, decreasing incidence of hospitalization, and also signifi cantly decreasing mortality in these patients [3,4]. The success of CRT depends on many factors such as appropriate location of the left ventricular (LV) electrode, and optimal timing of atrioventricular (AV) and VV delays [5,6]. Optimal programming of AV and VV delays plays an important role in reducing the proportion of patients who derive no apparent benefi t from CRT (the so called "non-responders"), despite correct positioning of the LV electrode [7].…”
Section: Introductionmentioning
confidence: 99%